Evaluation of Active Disease in a Patient of non-Hodgkin Lymphoma by PET-CT scan over non Significant CT, MRI Findings: a case report (Bangladesh Journal of Nuclear Medicine, 2019)
Imaging modalities like computed tomography (CT) and MRI (magnetic resonance imaging) have been used as diagnostic tools for decades for screening as well as staging for any malignancies but these scans provide anatomical information only. After introduction of 18 Flurodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) hybrid imaging modality as molecular imaging technique by measuring glucose metabolism has revolutionized the detection capability of tumor. PET-CT scan has been used in localization and staging of lymphoma for two decades worldwide. Here, a case of 52 years male, diagnosed case of non-Hodgkin lymphoma (NHL) and received chemotherapy. At the end of therapy results of conventional imaging by CT, MRI suggested complete response of the disease. However, simultaneous PET-CT scan showed extensive active disease. PET-CT hybrid imaging provides additive information about location and extent of the active tumor over CT & MRI, which have limitation to define functional lesion.Bangladesh J. Nuclear Med. 21(2): 125-128, July 2018